Comparative study of Fe-C-H interaction near line and point defects in iron structures - Simonetti, Sandra Isabel (2008)
The FeCH interaction near defects in iron structures was studied using qualitative structure calculations in the framework of the atom superposition and electron delocalization molecular orbital. Calculations were performed using three Fe clusters to simulate an edge dislocation, a divacancy; both in bcc iron and a stacking fault in an fcc iron structure. In all cases, the most stable location for C atom inside the clusters was determined. Therefore, H atom was approximated to a minimum energy region where the C atom resides. The total energy of the cluster decreases when the C atom is located near the defects zone. In addition, the presence of C in the defects zone makes no favorable H accumulation. The C acts as an expeller of H in a way that reduces the hydrogen FeFe bonds weakening.